2008
DOI: 10.1200/jco.2007.15.3858
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study Comparing Preoperative Radiotherapy With Chemoradiotherapy in Nonresectable Rectal Cancer

Abstract: CRT improved local control, time to treatment failure, and cancer-specific survival compared with RT alone in patients with nonresectable rectal cancer. The treatments were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
247
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(274 citation statements)
references
References 33 publications
7
247
1
9
Order By: Relevance
“…Three randomized controlled trials have all concluded that the addition of 5-FU to adjuvant RT in LARC improves local control and increases respectability, but without influencing survival or rate of sphincter preservation (18,46,47), with the exception of one trial showing increased disease-free survival in the most advanced nonresectable cancers (18). Importantly, these studies also show increased but tolerable acute toxicity (14).…”
Section: Adjuvant Chemoradiotherapy (Crt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Three randomized controlled trials have all concluded that the addition of 5-FU to adjuvant RT in LARC improves local control and increases respectability, but without influencing survival or rate of sphincter preservation (18,46,47), with the exception of one trial showing increased disease-free survival in the most advanced nonresectable cancers (18). Importantly, these studies also show increased but tolerable acute toxicity (14).…”
Section: Adjuvant Chemoradiotherapy (Crt)mentioning
confidence: 99%
“…The locally advanced tumors constitute at least 50% of all rectal carcinomas including the primary non-resectable tumors which constitute about 10-15% of all cases (18).…”
Section: Locally Advanced Rectal Cancer -Larcmentioning
confidence: 99%
“…These data lend support to the view that CRT is more effective than RT. A recent abstract also supports the use of 5-FU-based CRT in this setting [30].…”
Section: Unresectable Rectal Cancer: Randomized Trials Of Crt Versus mentioning
confidence: 99%
“…Зна-чимость неоадъювантного лечения показана в различных рандомизированных исследованиях, в которых были оп-тимизированы последовательность применения лекар-ственных препаратов, дозы лучевого воздействия и мето-дики хирургических вмешательств. Этот процесс растя-нулся более чем на три десятилетия [7,8].…”
unclassified